Series of Archaeological Dances (RABAM PHIMAIPURA): The Performance Arises from Historical Locations and Creativity Has Benefits for the Phimai District in Nakhon Ratchasima Province - Kaewprasert, Thucksin; Rompochuen, Patcharin (Interdisciplinary Academic and Research Journal, 2024)
Background and Aims: The RAMBAM PHIMAIPURA series of archaeology dances and performances spans more than three decades. The RAMBAM PHIMAIPURA plays an important role in Phimai District in terms of arts and culture, unity in human psychology, and other aspects. Nevertheless, neither the performance's provenance nor its worth can be determined with certainty from records or studies. The objectives of this research 2 are: 1) Examine the origins, composition, and history of the RAMBAM PHIMAIPURA or Series of Archaeological Dances. 2) Examine the worth of the Phimai District in the Series of RAMBAM PHIMAIPURA or Series of Archaeological Dances. Methodology: Qualitative research that begins with gathering information from documentaries, research, and fieldwork Then summarize, analyze, and present the research results in the form of a descriptive analysis. Results: 1) The RAMBAM PHIMAIPURA is an archaeological dance invented in 1988. The goal of Ms. Wanee Amatiratana's performances is to highlight regional features. The creative process of performance research and collecting both physical and abstract information is the first step in the performance development process. The dance has to be processed and designed in a second step. 2) The Phimai District benefits from RAMBAM PHIMAIPURA in five areas: academic, social and cultural, spiritual, belief, and economic. Conclusion: Information about Phimai Historical Park and the artist's motivation is the foundation of the archaeological dance series (RABAM PHIMAIPURA). Furthermore, the Phimai District benefits from the performance.